DAILY AND SEASONAL POPULATION LIFE CYCLE AND FLUCTUATION OF THE OVARY MOSQUITA Contarinia sorghicola (Coquillet) (Diptera: Cecidomyiidae) - CERMEÑO-L., GERMÁN F.; GALVAN-V., RICARDO; LOBATÓN-G., VALENTIN (Revista Colombiana de Entomología, 1984)
In order to study the life cycle and population fluctuations of the sorghum midge Contarinia sorghicola the present work was conducted during March to November 1983 at Universidad de Córdoba and at "Turipaná" research station (28°C, 80%, R.H., and 1200 mm rainfall). The result obtained showed that the egg stage lasts 41-52 hours. The larval stage 8 to 11 days, the pupa 3 to 5 days, the adult female 13.68 hours, and the adult male 8.64 hours. The total life cycle for the females ranged from 13.01 to 18.92 days and from 12.95 to 18.63 for the males. The highest infestation levels were found 4 to 10 days after the imitation of the anthesis and the adults were more abundant between 8 to 11 a.m.